A systematic literature review of crowdfunding and sustainability: highlighting what really matters - Alexa Böckel; Jacob Hörisch; Isabell Tenner (Management Review Quarterly, 2020)
This article systematically reviews literature at the intersection of crowdfunding and sustainability. It analyzes the extent to which the current research foci in crowdfunding and sustainability contribute to unleashing the potential of crowdfunding for sustainable development. The findings highlight that the research field has a relatively short history but already shows signs of growing maturity. With regard to the research foci, the results reveal misbalances between the relevance ascribed to various aspects in research and in practice. For example, the research primarily deals with the types of crowdfunding that make up the smallest shares of the crowdfunding volume. Likewise, a research gap related to the post-funding phase as well as to environmental oriented projects is identified. On this basis, it is recommended to focus future research on the impact of crowdfunding projects on staying within the planetary boundaries and on crowdfunding projects dealing with environmental issues or integrating the social and environmental dimension of sustainability. Additionally, the potential of crowdfunding as a legitimizing function for sustainable ventures needs to be researched.
Keywords: G24; G29; Q56; Q59; 650; Crowdfunding; Sustainability; Systematic literature review; Sustainable development; Sustainable entrepreneurship